1979
DOI: 10.1002/bjs.1800660324
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of a liver cell adenoma after long term Methyltestosterone: Report of a case successfully treated by emergency right hepatic lobectomy

Abstract: A case of spontaneous rupture of a liver cell adenoma is reported in a female transexual treated with methyltestosterone 150 mg daily for 7 years. Emergency right hepatic lobectomy was performed successfully. Histology showed peliosis hepatis also. Emergency resection of a liver cell adenoma has been reported in a young woman taking oral contraceptives, and an elective resection in another female transexual treated with methyltestosterone. However, to the best of our knowledge this is the first case of emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…76 The findings described by Paradinas et al 76 are similar but less severe than those seen in peliosis hepatis, which is a rare hemorrhagic liver disorder classically showing larger blood-filled spaces and hemorrhage, associated with numerous etiologies including anabolic steroid use. A case of fulminant peliosis hepatis was described in a transgender man by Bird et al 77 In addition, 3 cases of hepatocellular neoplasia have been reported in persons taking masculinizing hormones. The case reported by Bird et al 77 had a concurrent hepatic adenoma.…”
Section: Gastrointestinal Systemmentioning
confidence: 99%
“…76 The findings described by Paradinas et al 76 are similar but less severe than those seen in peliosis hepatis, which is a rare hemorrhagic liver disorder classically showing larger blood-filled spaces and hemorrhage, associated with numerous etiologies including anabolic steroid use. A case of fulminant peliosis hepatis was described in a transgender man by Bird et al 77 In addition, 3 cases of hepatocellular neoplasia have been reported in persons taking masculinizing hormones. The case reported by Bird et al 77 had a concurrent hepatic adenoma.…”
Section: Gastrointestinal Systemmentioning
confidence: 99%
“…Cases of hepatic dysfunction and malignancies have previously been observed among men using oral testosterone preparations (Bird, Vowles, & Anthony, 1979;Coombes, Reiser, Paradinas, & Burn, 1978;Futterweit, 1998;Nieschlag & Behre, 1998;Paradinas, Bull, Westaby, & Murray-Lyon, 1977), though a newer preparation of testosterone undecenoate dissolved in castor oil appears to be acceptably safe (Gooren & Bunck, 2004) and is used in Canada and parts of Europe.…”
Section: Masculinizing Hormone Therapy (Ftm): Physiological Consideramentioning
confidence: 99%
“…Transient elevation of liver enzymes that cannot be attributed to any other cause is found in approximately 3% of male‐to‐female transsexuals treated with oestrogens and persists for more than 6 months in half of these (van Kesteren et al ., 1997). Case reports of hepatomas (Paradinas et al ., 1977) and spontaneous rupture of a liver cell adenoma (Bird et al ., 1979) have been reported in female‐to‐male transsexuals treated with methyltestosterone, a form of male hormone no longer used.…”
Section: Specific Effects Of Cross‐sex Hormone Treatmentmentioning
confidence: 99%